Pengembangan Aplikasi Website Pokok Bahasan Ekosistem di Sekolah Dasar Brawijaya Smart School - Firda Dwi Cahyati; Agus Mukti Wibowo; Rizki Amelia (Universitas Islam Negeri Maulana Malik Ibrahim Malang)
The essence of Natural Science consists of products, processes, and attitudes. The scientific method at the elementary school level is learned gradually. One of them is by involving students to observe their surroundings. One of the science materials at the elementary school level is the ecosystem. Students' understanding of ecosystem material will be very good if students observe directly at the surrounding environment. However, the concept of food chains and food webs is very rarely found directly in the environment at one observation at a time. For that, a website-based learning media is needed on ecosystem materials for fifth grade students of SD Brawijaya Smart. School. This research is a research and development research with the Dick and Carey development model. The subject of this research validator involved one material expert, design expert and learning expert respectively. In addition, this study also involved 25 fifth grade students of SD Brawijaya Smart School to assess the attractiveness of the website application for students. The ecosystem material website application in class V SD Brawijaya Smart School fulfills the feasibility test of several validators. The results of the validation of material experts were 96%, design experts 96%, and learning experts 92%. These results indicate that the website developed is feasible / valid for use in the learning process. This research is limited to the process of developing a check dam to test the validity of the ecosystem website application in class V SD Brawijaya Smart School. Therefore, further research is needed to test the effectiveness of the ecosystem material website application on students' conceptual understanding.